Chicken IL-26 regulates immune responses through the JAK/STAT and NF-κB signaling pathways. (August 2017) - Truong, Anh Duc; Hong, Yeojin; Hoang, Cong Thanh; Lee, Janggeun; Hong, Yeong Ho
Abstract: Chicken interleukin 26 (ChIL-26), a member of the IL-10 family, is expressed in T cells and can induce expression of proinflammatory cytokines. We examined the response of signal transduction pathways to ChIL-26 stimulation in the chicken T (CU91), macrophage (HD11), and fibroblast (OU2) cell lines. ChIL-26 activated JAK2 and TYK2 phosphorylation, as well as activation of STAT1, STAT3, and SHP2 via tyrosine/serine residues. We also showed that ChIL-26 activates the phosphorylation of NF-κB1, TAK1, and MyD88 kinase, which are key regulators of NF-κB signaling pathways. Moreover, ChIL-26 stimulation upregulated mRNA expression of chemokines (CCL4, CCL20, and CXCL14), Th1 (IFN-α, IFN-β, IFN-γ, IL-1β, and IL-6), Th2 (IL-4 and IL-10), and Th17 (IL-12p40, IL-17A, and IL-17F), and the Treg cytokines (TGF-β4); additionally, it increased Th1 and Th17 protein levels and nitric oxide production but did not affect cell proliferation. Together, these results suggest that ChIL-26-induced activation of chemokines, Th1, Th2, and, Th17, and the Treg cytokines is mediated through JAK/STAT and NF-κB signaling pathways in chicken T, macrophage, and fibroblast cell lines. These results indicate a key role for ChIL-26-induced polarization of the immune response and could reveal new therapeutic approaches for use in combination with molecules that activate T and macrophage cells via activation JAK/STAT and NF-κB signaling pathways. Highlights: Chicken interleukin-26 (ChIL-26), a member of the IL-10 family. ChIL-26 activates JAK-STAT and NF-κB1 signaling pathway. ChIL-26-induced activation of the chemokines, Th1, Th2, Th17, and Treg cytokines. ChIL-26 increased Th1 and Th17 protein levels and nitric oxide production.